Effects of acid deposition on soil chemistry and plant growth - Ibrahim, Mohamad Hilmi (2013)
Emission of pollutant gases mainly SO2 and NOX has generated air pollution and acid deposition and the two principal sources of these pollutants are human and natural activities. Acid deposition has adverse effect on plants, soils, water and aquatic organisms. Thus, a study was conducted to determine acid deposition effects on soil properties and plant growth. The preliminary study was conducted by monitoring rainwater chemical characteristics and deposition rate using rainwater sampler. Monitoring was done at the Universiti campus for 104 days and rainwater was collected once every 13 days and analyzed for nutrient concentrations and deposition rate. For the soil study, 54 leaching columns were prepared and arranged in CRD design. A 318 mL of rainwater at different pH was applied up to 4, 7 and 15 applications for 45 days. At day 45, soil and leachate samples were collected and analyzed. Acid deposition effect on plant growth was determined using Shorea macroptera and Sandoricum koetjape as the test plants. The seedlings were treated with 618 mL of rainwater at different pH for the entire study period and growth parameters were observed once every 30 days up to three months. The amount of ion deposition in the rainfall and through-fall were quantified using resin sampler. Assessment was done in the rehabilitated forest and an open area once in 6 months for a year. Resin was collected and analyzed for nutrient concentration. The amount of ion deposition was calculated using a formulas suggested by EANET. The pH of rainwater ranged from 5.8 to 6.5. Deposition rate was lower for higher volume of rainwater especially for cations and sulfide. For the leaching study, higher pH of rainwater reduced CEC and K concentrations but increased Cu, Fe and SO4 concentrations in the soil. In the case of leachate, low rainwater pH increased pH, Na, Cu and NO2 but EC and salinity decreased. The growth of Shorea macroptera and Sandoricum koetjape was retarded in terms of height, number of leaves and biomass. Chlorosis and necrosis appeared as the rainwater pH decreased from 6.00 ± 0.2 to 3.5. At the same time, it affected P and Ca in S. macroptera and N, Ca, Mg, Zn and Fe in S. koetjape plant parts. For soil, low SAR pH affected in terms of pH, Fe, Cu, Zn, acidity, H, Al, K and SO4. The resin sampler recorded higher deposition of Na, Mg, Fe, Zn and NH4 in the rehabilitated forest compared to the open area. However Ca, Cu, NO3 and SO4 deposition was high in the open area compared to the rehabilitated forest. In conclusion, acid rain affects plant growth and soil chemical properties. Higher rainwater pH in the study area indicated that the area is not still affected by acid deposition.